(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to examine the role of coaches in developing students’ character through futsal extracurricular activities at SMK KBU. The study used a quantitative approach with a pre-experimental design in the form of a one-shot case study. The research subjects consisted of 23 students who actively participated in futsal extracurricular activities. Data were collected through a questionnaire on students’ perceptions regarding the role of coaches and character development, then analyzed descriptively using average values ​​and percentages. The results showed that the role of coaches was in the very good category with a percentage of 88.14%, while student character development was also in the very good category with a percentage of 87.40%. These findings indicate that coaches not only play a role in developing futsal technical skills, but also contribute significantly in instilling character values ​​such as discipline, responsibility, cooperation, sportsmanship, and self-confidence. This study provides an empirical contribution that extracurricular sports activities, especially futsal, can be a strategic tool in strengthening character education in vocational high schools.